Interface studies by simulation on methylammonium lead iodide based planar perovskite solar cells for high efficiency. (15th September 2019) - Jeyakumar, R.; Bag, Atanu; Nekovei, Reza; Radhakrishnan, R.
Graphical abstract: Highlights: The influence of energy band discontinuity on efficiency has been analyzed. The role of blocking layers is explained by using energy band diagram. An optimum band gap is suggested for high efficiency. Abstract: Perovskite solar cells gained importance in the recent years due to high power conversion efficiency and low-cost fabrication methods. Suitable solar cell properties can be obtained by fine tuning process parameters. Charge transport, optical band gap of perovskite absorber and energy band discontinuity on either side of absorber are an important factor in determining cell efficiency. In this work, theoretical studies on cell efficiency were performed as a function of absorber band gap since it determines band discontinuity. Band alignment investigation was performed to minimize band discontinuity between interfaces. Our results show that, valance band discontinuity at HTL/absorber interface (ΔEv1 ) increases from 0.01 eV to 0.42 eV as the absorber band gap increases from 1.20 eV to 1.65 eV. On the other hand, valance band discontinuity at absorber/ETL interface (ΔEv2 ) decreases from 2.07 eV to 1.62 eV. Conduction band discontinuity on both sides of absorber interface is almost constant and independent of absorber band gap. The increase in ΔEv1 restricts holes collection which in turn affects cell efficiency. Depending upon ΔEv1, cell efficiency increased from 24.96% to 29.40% and then decreased to 26.27%. This is due to the fact that maximum acceptable limit for ΔEv1 is 0.20 eV and holes can reach back electrode when ΔEv1 ≤ 0.20 eV. For the absorber band gap of 1.40 eV with ΔEv1 of 0.17 eV, a high efficiency of 29.40% has been obtained with Jsc of 28.70 mA/cm 2, Voc of 1.24 V, and FF of 82.60%.